Period Estimation of PN Sequence for Weak DSSS Signals Based on Improved Power Spectrum Reprocessing in Non-cooperative Communication Systems - Zhang Yu; Wu Hao; Chen Yong (2012 International Conference on Control Engineering and Communication Technology, 2012)
To solve the period estimation of pseudo-noise (PN) sequence of direct sequence spread spectrum (DSSS) signals with low signal to noise rates (SNR) in non-cooperative communication systems, this paper presents a wavelet decomposition-based power spectrum reprocessing method with accumulation to estimate the period of PN sequence for weak DSSS signals. Firstly, the wavelet decomposition is employed to preprocess the DSSS signals with noise instead of the pre-filter when the optimal re-filter can't design without any prior knowledge. Then the period of PN sequence is estimated by power spectrum reprocessing with accumulation. Theory analysis and simulation results show that the proposed method can accurately estimate the period of PN sequence with very low SNR in non-cooperative communication.